Specific thylakoid protein phosphorylations are prerequisites for overwintering of Norway spruce (Picea abies) photosynthesis - Steffen Grebe; Andrea Trotta; Azfar Ali Bajwa; Ilaria Mancini; Pushan Bag; Stefan Jansson; Mikko Tikkanen; Eva-Mari Aro (NATL ACAD SCIENCES, 2026)
Coping of evergreen conifers in boreal forests with freezing temperatures on bright winter days puts the photosynthetic machinery in great risk of oxidative damage. To survive harsh winter conditions, conifers have evolved a unique but poorly characterized photoprotection mechanism, a sustained form of nonphotochemical quenching (sustained NPQ). Here we focused on functional properties and underlying molecular mechanisms related to the development of sustained NPQ in Norway spruce (Picea abies). Data were collected during 4 consecutive years (2016 to 2019) from trees growing in sun and shade habitats. When day temperatures dropped below -4 degrees C, the specific N-terminally triply phosphorylated LHCB1 isoform (3p-LHCII) and phosphorylated PSBS (p-PSBS) could be detected in the thylakoid membrane. Development of sustained NPQ coincided with the highest level of 3p-LHCII and p-PSBS, occurring after prolonged coincidence of bright winter days and temperatures close to -10 degrees C. Artificial induction of both the sustained NPQ and recovery from naturally induced sustained NPQ provided information on differential dynamics and light-dependence of 3p-LHCII and p-PSBS accumulation as prerequisites for sustained NPQ. Data obtained collectively suggest three components related to sustained NPQ in spruce: 1) Freezing temperatures induce 3p-LHCII accumulation independently of light, which is suggested to initiate destacking of appressed thylakoid membranes due to increased electrostatic repulsion of adjacent membranes; 2) p-PSBS accumulation is both light -and temperature-dependent and closely linked to the initiation of sustained NPQ, which 3) in concert with PSII photoinhibition, is suggested to trigger sustained NPQ in spruce.